Mechanical and thermal properties of bio-composites based on polypropylene reinforced with Nut-shells of Argan particles - Essabir, H.; Hilali, E.; Elgharad, A.; El Minor, H.; Imad, A.; Elamraoui, A.; Al Gaoudi, O. (Materials in engineering, 2013)
► Nuts-shells of Argan particles are used as reinforcement in thermoplastic matrix. ► Particles are homogeneously dispersed and distributed within PP matrix. ► Mechanical and thermal characterization of the composite are applied. ► Particles–matrix adhesion was assured by the use of a SBS compatibilizer. This study treats the combined effects of both particle sizes and particle loading on the mechanical and thermal properties of polypropylene (PP) composites reinforced with Nut-shells of Argan (NA) particles. Three range sizes of particles were used in the presence of a polypropylene matrix grafted with 8wt.% of a linear block copolymer based on styrene and butadiene coupling agent, to improve adhesion between the particles and the matrix. The composites were prepared through melt-blending using an internal mixer and the tensile specimens were prepared using a hot press molding machine. Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FT-IR), Thermo Gravimetric Analysis (TGA), Differential Thermal Analysis (DTA) and tensile tests were employed to characterize the composites at 10, 15, 20 and 25wt.% particle contents. Results show a clear improvement in Young’s modulus from the use of particles when compared to the neat PP, a gain of 42.65%, 26.7% and 2.9% at 20wt.% particle loading, for particle range 1, 2 and 3, respectively. In addition a notable increase in the Young’s modulus was observed when decrease the particle size. The thermal stability of composites exhibits a slight decrease (256–230°C) with particles loading from 10 to 25wt.%, against neat PP (258°C).